Current evaluation and management of patients with chronic rhinosinusitis and nasal polyps. (2nd December 2022) - Ceballos Cantu, Juan Carlos; Alobid, Isam; Mullol, Joaquim
ABSTRACT: Introduction: A clear understanding of the pathophysiology of chronic rhinosinusitis with nasal polyps (CRSwNP) and its close association with other airway pathologies, especially asthma, helps to comprehend the concept of the united airway and the importance of a multidisciplinary approach and the actual roll of biologic therapy. Areas covered: This expert review is the synthesis of a working group on the current state of the art of the evaluation and management of CRSwNP. A thorough analysis of the literature has been conducted for the latest studies and results, specially the European (EPOS 2020) and American (ICAR-RS 2021) guidelines. Expert opinion: The roles of optimal medical treatment and indications for surgery are becoming clearer, but much research is still needed regarding the extent and radicality when surgery is indicated. The main objectives of this review were to provide a clear and updated description of treatments, their indication, follow-up, and response criteria. These steps are considering the broad spectrum of inflammation endophenotypes and the biologic therapy available. Understanding the role and limitations of each specialty is key for providing greatest benefit to the patient.